Discovery of a supposed extinct settlement species made at Königsmühle in the Ore Mountains - Petr Mikšíček (Envigogika, 2014)
In one of my speeches on the Ore Mountains at the Green Network Conference in Dresden in 2`011, I referred to the Ore Mountain region as a landscape full of footprints. Footprints left here by bygone generations of inhabitants as well as present-day footprints left by us. Footprints can be cast in plaster and preserved for future generations, or wiped out, hidden, erased from our memory. Both these approaches have been applied in the Ore Mountains. The preservation of these footprints clashes against the interests of land owners. The association DoKrajin, in which I work, tries to preserve the footprints, so I will gladly share with you a story of an ancient footprint that is on the brink of being wiped out.